PENGARUH REALISTIC MATHEMATIC EDUCATION (RME) DAN TEAM GAMES TOURNAMENT (TGT) SERTA MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Putri, Restu; Rufi’i; Reza Rachmadtullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Realistic Mathematics Education (RME) and Teams Games Tournament (TGT) learning models on the mathematics proficiency of fifth-grade students and their interaction with learning motivation. The background of this research is the low mathematics ability of Indonesian students, as reflected in PISA results, which remain below the global average. The research employed a 2x2 factorial experimental design involving 139 students grouped based on the learning model (RME or TGT) and motivation levels (high or low). The results showed that the RME model (average score 85.4) was more effective than the TGT model (average score 82.7). Moreover, students with high motivation achieved a higher average score of 88.1 compared to those with low motivation (average score 79.3). ANOVA tests revealed significant effects from the learning model (F=25.67, p<0.05), learning motivation (F=30.45, p<0.05), and their interaction (F=18.23, p<0.05). This study highlights the importance of innovative learning models like RME and TGT to improve mathematics learning outcomes. Its implications include recommendations for educators to integrate interactive and meaningful approaches that address diverse learning needs. It also encourages further research to develop innovative methods in primary education, particularly to enhance students' preparedness for future learning challenges.